Buys Ballot Approach in Time Series Analysis of Typhoid Fever - Dalatu, Paul I.; Ibrahim, Asabe (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2023)
Typhoid fever (is also called enteric fever) is a bacterial disease spread through contaminated food, water or close contact. However, where it is prevalence government usually recommend vaccines to curtail its deadly spreading in the affected area. The fever is caused by Salmonella typhi bacteria. Therefore, we had adopted the Buys Ballot approach by using time series analysis for the estimation of trend of typhoid fever disease from the year 2011 to 2020 and predicts the future occurrence of the disease in Mubi South Local Government Area (LGA) of Adamawa State, Nigeria. However, based on the data used the result shows that there is significant increase in the recorded cases of typhoid fever disease, it has forecasted and predicted that more number of people may be affected in future compared to the study results obtained. Hence, this study has given some recommendations in order to reduce the prevalence of typhoid fever disease in future